2010
DOI: 10.3163/1536-5050.98.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Case study: the Health SmartLibrary experiences in web personalization and customization at the Galter Health Sciences Library, Northwestern University

Abstract: Users did not always take advantage of the services designed to aid their library research experiences. When personalization is available at registration, users readily accepted it. Customization tools were used less frequently; however, more research is needed to determine why this was the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In contrast, the adaptive approach is generally perceived to be more favorable among users. Results of a five-year study at the Galter Health Sciences Library "indicated that users were receptive to personalized resource selection and that the automated application of specialty-based, personalized HSLs was more frequently adopted than manual customization by users" (Shedlock et al, 2010). This supports the results of earlier studies where users preferred adaptive over adaptable personalization (Frias-Martinez et al, 2006.…”
Section: Using Personalization To Create a User-centric Library Web Sitesupporting
confidence: 62%
“…In contrast, the adaptive approach is generally perceived to be more favorable among users. Results of a five-year study at the Galter Health Sciences Library "indicated that users were receptive to personalized resource selection and that the automated application of specialty-based, personalized HSLs was more frequently adopted than manual customization by users" (Shedlock et al, 2010). This supports the results of earlier studies where users preferred adaptive over adaptable personalization (Frias-Martinez et al, 2006.…”
Section: Using Personalization To Create a User-centric Library Web Sitesupporting
confidence: 62%
“…Shedlock et al discuss one library's experience when users were offered the opportunity to customize access to library online holdings, and relatively few took advantage of the opportunity [4]. Just as it is hard to improve commoditized products like gasoline or toasters, improving the technology that delivers information can be very difficult.…”
mentioning
confidence: 99%
“…Dempsey, 2003;Kalyanaraman and Sundar, 2006;Nicols and Mellinger, 2007;Shedlock et al, 2010). Brophy (2007, pp.…”
Section: The Implications For Collection Developmentmentioning
confidence: 99%